2020
DOI: 10.3390/w12051306
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Textile Wastewater by CAS, MBR, and MBBR: A Comparative Study from Technical, Economic, and Environmental Perspectives

Abstract: In this study, three different biological methods—a conventional activated sludge (CAS) system, membrane bioreactor (MBR), and moving bed biofilm reactor (MBBR)—were investigated to treat textile wastewater from a local industry. The results showed that technically, MBR was the most efficient technology, of which the chemical oxygen demand (COD), total suspended solids (TSS), and color removal efficiency were 91%, 99.4%, and 80%, respectively, with a hydraulic retention time (HRT) of 1.3 days. MBBR, on the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…The microbial community data indicate that augmentation of CES-1 carrying Gluconacetobacter_unclassified and Acetobacter_unclassified as dominant species allowed a good selection of a greater number of species, leading to a higher diversity index (Shannon indices: 2.11–3.25) in the later stages of augmentation compared with before augmentation and at the early stage of augmentation (Shannon indices: 1.24–2.61). A large number of unclassified sequences were found in dye wastewater [ 41 ], suggesting that a wide variety of novel species may inhabit in the dye wastewater treatment system [ 42 ]. It is suggested that many degrading microbes appeared to be enriched in B, PA, SA, and SD in the later stages of augmentation because of long term bioaugmentation of CES-1 into SD.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial community data indicate that augmentation of CES-1 carrying Gluconacetobacter_unclassified and Acetobacter_unclassified as dominant species allowed a good selection of a greater number of species, leading to a higher diversity index (Shannon indices: 2.11–3.25) in the later stages of augmentation compared with before augmentation and at the early stage of augmentation (Shannon indices: 1.24–2.61). A large number of unclassified sequences were found in dye wastewater [ 41 ], suggesting that a wide variety of novel species may inhabit in the dye wastewater treatment system [ 42 ]. It is suggested that many degrading microbes appeared to be enriched in B, PA, SA, and SD in the later stages of augmentation because of long term bioaugmentation of CES-1 into SD.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the evaporation and the adsorption of water into the fiber causes 30% of the water loss during textile production. The quality of the dyes with 100% reused water (ideal reuse) was analyzed to evaluate the possibility of achieving a fully circular dyeing process; however, it would only represent 70% of the input water [40]. Our previous work studied the reuse of the treated water by the hybrid MBBR-MBR, applying tone changes indicating the color differences and the reuse of salt [35].…”
Section: Reuse Of the Treated Watermentioning
confidence: 99%
“…[71], and the photosynthetic bacterium Rhodopseudomonas palustris [80]. Inoculating an MBBR with sludge from a WWTP treating dye-containing wastewaters is also a strategy to achieve aerobic color removal, possibly because of the existence of a microbial community adapted to dyes and, therefore, able to synthesize specific enzymes and use the dye as a carbon source [69,87].…”
Section: Cellmentioning
confidence: 99%
“…The moving bed biofilm reactor (MBBR) is an example of a biofilm technology in growing expansion over the world. Recent studies have shown that this biofilm technology may be efficient for the treatment of dye-containing effluents [65,71,87]. However, the number of studies addressing the application of the MBBR process for this purpose is limited.…”
Section: Introductionmentioning
confidence: 99%